Gynecologic Oncology Sub-Specialty Training in Ghana: A Model for Sustainable Impact on Gynecologic Cancer Care in Sub-Saharan Africa - Anna Sarah Erem; Adu Appiah-Kubi; Adu Appiah-Kubi; Thomas Okpoti Konney; Thomas Okpoti Konney; Kwabena Amo-Antwi; Sarah G. Bell; Timothy R. B. Johnson; Carolyn Johnston; Alexander Tawiah Odoi; Alexander Tawiah Odoi; Emma R. Lawrence (Frontiers Media S.A., 2020)
African women have double the risk of dying from cancer than women in high-income countries. In Ghana, most women with gynecological malignancies present with advanced-stage disease when treatment is less effective. Barriers to improved cancer outcomes include the availability of cancer screening, affordability of treatment, and access to gynecologic oncology specialists. In response to a paucity of gynecologic oncology providers, an in-country fellowship training program was established at Komfo Anokye Teaching Hospital (KATH) in 2013. Historically, Ghanaian resident physicians were sent to other countries for fellowship training and were unlikely to repatriate. The establishment of an in-country training program not only addresses the challenge of "brain drain," but also builds local capacity in gynecologic oncology education and emphasizes culturally relevant and accessible healthcare. The four-years gynecologic oncology fellowship program at KATH was developed as part of a longitudinal multi-decade partnership between the University of Michigan and academic medical centers in Ghana. The fellowship trains obstetricians and gynecologists to provide subspecialist clinical and surgical care to patients with gynecologic malignancies. Fellows collaborate with the radiation, oncology and pathology departments, participate in monthly inter-institutional tumor board meetings, conduct research, advise on health policy issues, and train subsequent cohorts. This fellowship is representative of emerging twenty-first-century trends in which subspecialty training programs in low-income countries are strengthened by international collaborations. Providing specialized training in gynecologic oncology can help develop and maintain resources that will improve clinical outcomes for women in low-resources settings.